High thermal conductivity layered phase change composites
By using layered phase change composite materials in electronic devices, the challenge of thermal management of electronic devices when designs are getting smaller and thinner is solved, achieving more efficient thermal management and longer life.
Patent Information
- Application Number
- CN202180008207.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-08
- Filing Date
- 2021-01-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-01-05
AI Technical Summary
Existing electronic devices face challenges in thermal management when designs are getting smaller and thinner, especially in the case of increased heat generation caused by denser electronic components.
A layered phase change composite material is developed, including a phase change material, a plurality of boron nitride particles and a phase change layer, and a first and a second covering layer are provided on both sides of the phase change layer. By vibrating on the three-way vibration table to form a phase change layer, the orientation of the boron nitride particles improves thermal conductivity.
The material significantly increases the heat in and out rate, improves heat management, reduces heat accumulation, extends the life of the electronic device, and provides better management of temperature intermittent phenomena.
Smart Images

Figure CN114929833B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 62 / 958,644, filed on January 8, 2020. The related application is incorporated herein by reference in its entirety. Background Art
[0003] The circuit designs of electronic devices such as televisions, radios, computers, medical instruments, business machines, and communication equipment have become increasingly smaller and thinner. The increased power of such electronic components has resulted in increased heat generation. In addition, smaller electronic components are more densely packed into increasingly smaller spaces, resulting in even greater heat generation. At the same time, temperature-sensitive components in electronic devices often need to be maintained within specified operating temperatures to avoid significant performance degradation or even system failure. Therefore, manufacturers continue to face the challenge of dissipating the heat generated in electronic devices.
[0004] There continues to be a need for new approaches to thermal management in various devices, particularly electronic devices, and there is an increasing demand for electrically insulating materials with enhanced heat dissipation capabilities. Summary of the invention
[0005] Disclosed herein are layered phase change composite materials having high thermal conductivity.
[0006] In one aspect, a layered phase change composite material includes: a phase change layer including a phase change material, a plurality of boron nitride particles, and a binder; and a first cover layer and a second cover layer on opposite (two) sides of the phase change layer.
[0007] In another aspect, the method of manufacturing the layered phase change composite material includes: forming a first covering layer from a first composition; forming a phase change layer from the phase change composition, wherein forming the phase change layer includes vibrating the phase change composition on a 3-way vibration table; and forming a second covering layer from a second composition.
[0008] In yet another aspect, an article may include the layered phase change composite material.
[0009] The above described and other features are exemplified by the following figures, detailed description, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] The drawings are of exemplary embodiments, wherein like elements are numbered alike.
[0011] Figure 1 is a diagram of one embodiment of a high thermal conductivity layered phase change composite material;
[0012] Figure 2 is a microscopic image of a top view of the phase change layer of Example 1 after curing; and
[0013] Figure 3 is a scanning electron microscopic image of a cross section of the layered phase change composite material of Example 1. DETAILED DESCRIPTION
[0014] Phase change material (PCM) is a substance with a high heat of fusion that can absorb and release large amounts of latent heat during phase transitions such as melting and solidification, respectively. During the phase change, the temperature of the phase change material (referred to herein as the transition temperature) can remain almost constant, substantially inhibiting or preventing the flow of thermal energy through the material. In this way, heat can be reversibly stored and removed by the phase change material. Although a solid block of a phase change material has a very large theoretical heat absorption capacity, the process is generally not rapid due to the difficulty of heat transfer throughout the material. Therefore, it is challenging to develop articles containing phase change materials for various applications in which heat needs to be transferred into and out of the material more quickly.
[0015] In order to improve the heat transfer in and out of the phase change material, a layered phase change composite material including a phase change layer has been developed. The phase change layer comprises a phase change material, a plurality of boron nitride particles and a binder. The inclusion of boron nitride particles in the phase change layer unexpectedly increases the transfer rate of heat in and out of the phase change layer. The combination of boron nitride particles and phase change materials can be particularly advantageous for use as a thermal management material, especially in electronic devices, where the high crystallinity of the phase change material can allow a combination of high latent heat capacity and energy absorption, while boron nitride can introduce higher thermal conductivity and electrical insulation. This combination of properties can result in improved thermal management, lower heat accumulation, fewer problems, and can allow better management of temperature intermittent phenomena. The layered phase change composite material can provide improved thermal stability for the article, thereby reducing the degradation of performance and increasing the life of the article.
[0016] It was further found that if the phase change layer is formed while vibrating in three directions, the boron nitride particles in the phase change material, especially the small pieces of boron nitride particles, can be oriented in a direction perpendicular to the wide surface of the phase change layer. The vertical orientation of the boron nitride particles can lead to a further improvement in the thermal conductivity of the phase change layer.
[0017] Figure 1 One embodiment of a layered phase change composite material including a phase change layer having a first cover layer and a second cover layer on opposite sides of the phase change layer is shown in FIG. Figure 1A phase change layer 50 comprising a plurality of boron nitride particles 52 and a phase change material 54 is shown. Cover layers 10 and 20 are located on opposite sides of the phase change layer 50. The first cover layer 10 comprises a first plurality of boron nitride particles 12 in a first polymer 14, and the second cover layer 20 comprises a second plurality of boron nitride particles 22 in a second polymer 24. The first cover layer 10 and the second cover layer 20 are in direct physical contact with the phase change layer 50. The thickness of the phase change layer 50 can be 0.05 millimeters (mm) to 10 mm, or 0.5 mm to 2 mm, or 0.5 mm to 1.5 mm. The layer thickness of the first cover layer 10 and the second cover layer 20 can each independently be 0.001 mm to 1 mm or 0.01 mm to 0.5 mm.
[0018] The heat of fusion of the layered phase change composite material measured according to ASTM D3418-15 can be at least 50 joules per gram (J / g), or at least 75 J / g, or at least 100 J / g, or at least 240 J / g, or 50 J / g to 150 J / g. The thermal conductivity of the layered phase change composite material measured according to ASTM D5470-17 can be greater than 0.5 Watts / meter Kelvin (W / mK), or 0.5 W / mK to 1 W / mK.
[0019] Phase change materials have characteristic transition temperatures. The term "transition temperature" refers to the approximate temperature at which a material undergoes a transition between two states. The transition temperature may refer to a single temperature or to a temperature range at which the transition occurs, such as in the case of paraffin. The selection of a phase change material may depend on the transition temperature desired for the specific application that will contain the phase change material. For example, a phase change material with a phase transition temperature close to normal body temperature or about 37 degrees Celsius (°C). The transition temperature of a phase change material may be -5°C to 150°C, where such a temperature may be desirable for electronic applications to prevent user injury and protect components from overheating. However, typically, the transition temperature of a phase change material may be -100°C to 150°C, or -5°C to 150°C, or 0°C to 90°C, or 30°C to 70°C, or 35°C to 50°C. The transition temperature of a phase change material may be 25°C to 105°C, or 28°C to 60°C, or 45°C to 85°C, or 60°C to 80°C, or 80°C to 100°C. The phase change temperature of the phase change material may be 5° C. to 70° C., 20° C. to 65° C., 25° C. to 60° C., or 30° C. to 50° C., or 35° C. to 45° C. For use in LEDs and electronic components, in particular, the transition temperature of the phase change material incorporated into the phase change composition may be 0° C. to 115° C., 10° C. to 105° C., 20° C. to 100° C., or 30° C. to 95° C.
[0020] The transition temperature can be widened or narrowed by changing the purity of the phase change material, changing the molecular structure, blending two or more phase change materials, or any combination thereof. For example, a phase change material comprising at least two or more different phase change materials can exhibit two or more different transition temperatures or a single changed transition temperature. Having multiple transition temperatures or wide transition temperatures can be advantageous because the amount of heat transferred as latent heat can be increased, thereby delaying the transfer of sensible heat. Therefore, a phase change material having multiple transition temperatures or wide transition temperatures can more effectively help heat to be conducted away from adjacent components by overlapping or staggering heat absorption. For example, if a phase change composition comprises a first phase change material (PCM1) absorbed at 35°C to 40°C and a second phase change material (PCM2) absorbed at 38°C to 45°C, once the phase change composition reaches a temperature of 35°C, PCM1 can begin to absorb heat as latent heat until its phase change is complete, during which time PCM2 will begin to absorb heat as latent heat until its phase change is complete at a temperature of 45°C, thereby increasing the temperature range in which heat is absorbed as latent heat.
[0021] It should be noted that the ability of a phase change material to absorb heat as latent heat during a phase change is short-lived and further heat transfer after the phase change causes an increase or decrease in sensible heat, thereby raising or lowering the temperature of the phase change material.
[0022] The selection of phase change material can be based on its latent heat of fusion or the amount of energy absorbed or released per unit material when the phase change material undergoes its phase change. The latent heat of fusion of the phase change material can be at least 20 joules per gram (J / g), or at least 40J / g, or at least 50J / g, or at least 70J / g, or at least 80J / g, or at least 90J / g, or at least 100J / g. The latent heat of fusion of the phase change material can be 50J / g to 400J / g, or 60J / g to 400J / g, or 80J / g to 400J / g, or 100J / g to 400J / g. The latent heat of fusion of the phase change material can be greater than or equal to 150J / g, or greater than or equal to 180J / g, or greater than or equal to 200J / g. The heat of fusion of the phase change material can be determined by differential scanning calorimetry according to ASTM D3418-15.
[0023] Phase change materials that can be used include various organic substances and inorganic substances. Phase change materials may include at least one of the following: organic compounds (e.g., straight-chain alkanes or chain alkanes, branched alkanes, unsaturated hydrocarbons (e.g., alkenes or alkynes), alicyclic hydrocarbons, halogenated hydrocarbons (e.g., 1-halides), or aromatic compounds or aromatic hydrocarbons), fatty acids (e.g., caproic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, or cerotic acid), dibasic acids, fatty acid esters (e.g., methyl caprylate, methyl caprate, methyl laurate, methyl myristic acid, methyl palmitate, methyl stearate, methyl arachidic acid, methyl behenate, or methyl lignoceric acid), methyl esters, dibasic esters, alcohols (e.g., primary alcohols, methyl ester ... , secondary alcohols, tertiary alcohols, polyols (e.g., 2,2-dimethyl-1,3-propanediol, 2-hydroxymethyl-2-methyl-1,3-propanediol, ethylene glycol, polyethylene glycol, pentaerythritol, dipentaerythritol, pentaglycerine, tetramethylolethane, neopentyl glycol, tetramethylolpropane, 2-amino-2-methyl-1,3-propanediol, monoaminopentaerythritol, diaminopentaerythritol, or tris(hydroxymethyl)acetic acid), fatty alcohols (e.g., caprylic alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, lignocerol, wax alcohol, montanol, myristyl alcohol, and tetratriacontol) alcohol), sugar alcohol (e.g., erythritol, D-mannitol, galactitol, xylitol, or D-sorbitol), hydrated salt (e.g., calcium chloride hexahydrate, calcium bromide hexahydrate, magnesium nitrate hexahydrate, lithium nitrate trihydrate, potassium fluoride tetrahydrate, ammonium alum, magnesium chloride hexahydrate, sodium carbonate decahydrate, disodium phosphate dodecahydrate, sodium sulfate decahydrate, or sodium acetate trihydrate), polymer (e.g., polyethylene, poly(ethylene glycol), polypropylene, poly(propylene glycol), poly(tetramethylene glycol), poly(propylene malonate)) malonate), poly(neopentyl glycol sebacate), poly(pentyl glutarate), poly(vinyl myristate), poly(vinyl stearate), poly(vinyl laurate), poly(hexadecyl methacrylate), poly(octadecyl methacrylate), polyester produced by polycondensation of a diol (or a derivative thereof) and a diacid (or a derivative thereof), copolymers (e.g., polyacrylates or poly(meth)acrylates having alkyl hydrocarbon side chains or having polyethylene glycol side chains, or copolymers comprising at least one of polyethylene, poly(ethylene glycol), polypropylene, polypropylene glycol, or poly(tetramethylene glycol)), anhydrides (e.g., stearic anhydride), silicone wax, inclusion compounds, semi-inclusion compounds, gas inclusion compounds, ethylene carbonate, oils (e.g., vegetable oils (e.g., soybean oil, palm oil, or castor oil)), water, or metals. The phase change material may include an oil that may be purified or otherwise treated to make it suitable for use as a phase change material. The phase change material used in the phase change composition may be an organic substance.
[0024] The phase change material may include at least one of an alkane, a fatty acid, or a fatty acid ester. The alkane may have a formula C n H n+2 , wherein n can be 10 to 44 or 10 to 36. The transition temperature and the heat of fusion of homologous paraffins, homologous fatty acids or homologous fatty acid esters can be directly related to the carbon number. Phase change material can include at least one of paraffins, fatty acids or fatty acid esters with 15 to 40 carbon atoms, 18 to 35 carbon atoms or 18 to 28 carbon atoms. Phase change material can be a single paraffin, fatty acid or fatty acid ester, or a mixture of hydrocarbons, fatty acids or fatty acid esters. Phase change material can include vegetable oil.
[0025] The amount of phase change material in the phase change layer may depend on the type of phase change material used, the desired transition temperature, the type of boron nitride used, and other considerations. Based on the total volume of the phase change layer, the amount of phase change material in the phase change layer may be 1 volume percent (volume %) to 99 volume %, or 50 volume % to 99 volume %, or 80 volume % to 95 volume %. Based on the total volume of the phase change layer, the amount of phase change material in the phase change layer may be at least 65 volume %, at least 70 volume %, at least 75 volume %, at least 80 volume %, at least 85 volume %, at least 90 volume %, or at least 95 volume %, and not more than 99.9 volume %, not more than 98 volume %, not more than 97 volume %, or not more than 95 volume %. Based on the total volume of the phase change layer, the first cover layer and the second cover layer may each independently contain 0 volume % to 5 volume % or 0 volume % to 1 volume % of the phase change material.
[0026] The phase change layer, the first cover layer and the second cover layer may each independently contain a binder. Based on the total volume of the phase change layer, the phase change layer may contain 0.5 volume % to 15 volume % or 1 volume % to 6 volume % of the binder. Based on the total volume of each cover layer, the first cover layer and the second cover layer may each independently contain 10 volume % to 100 volume %, or 30 volume % to 70 volume %, or 30 volume % to 50 volume % of the binder. The binder may include at least one of a thermoplastic polymer or a thermosetting polymer. The binder may include at least one of polystyrene, epoxy resin, polybutadiene or polyisoprene.
[0027] The thermoplastic polymer may include at least one of the following: a polyolefin (e.g., a cyclic olefin polymer), a fluoropolymer, a polyacetal, a poly(C 1-6 alkyl) acrylate, polyacrylamide, polyacrylonitrile, polyamide, polyamideimide, polyanhydride, polyarylene ether, polyarylene ether ketone, polyarylene ketone, polyarylene sulfide, polyarylene sulfone, polybenzothiazole, polybenzo Azoles, polybenzimidazoles, polycarbonates, polyesters, polyetherimides, polyimides, poly(C 1-6 Alkyl) methacrylate, polymethacrylamide, poly oxadiazole, polyoxymethylene, polyphthalide, polysilazane, polysiloxane, polystyrene, polysulfide, polysulfonamide, polysulfonate, polythioester, polytriazine, polyurea, polyurethane or vinyl polymer.
[0028] Thermosetting polymers are derived from thermosetting monomers or prepolymers (resins) that can be irreversibly hardened and rendered insoluble by polymerization or curing, which can be initiated by heat or exposure to radiation, such as ultraviolet light, visible light, infrared light, or electron beam (e-beam) radiation. Thermosetting polymers include alkyd resins, bismaleimide polymers, bismaleimide triazine polymers, cyanate polymers, benzocyclobutene polymers, benzophenone Oxazine polymers, diallyl phthalate polymers, epoxy resins, hydroxymethyl furan polymers, melamine-formaldehyde polymers, phenolic resins (including phenol-formaldehyde polymers such as linear novolacs and resols), benzophenone Oxazines, polydienes such as polybutadiene (including homopolymers and copolymers thereof, such as poly(butadiene-isoprene)), polyisocyanates, polyureas, polyurethanes, triallyl cyanurate polymers, triallyl isocyanurate polymers, certain silicones, and polymerizable prepolymers (e.g., prepolymers having ethylenic unsaturation, such as unsaturated polyesters, polyimides), etc. The prepolymers can be polymerized, copolymerized or cross-linked, for example, with the following reactive monomers: for example, styrene, α-methylstyrene, vinyltoluene, chlorostyrene, acrylic acid, (meth)acrylic acid, acrylic acid (C 1-6 alkyl) esters, methacrylate (C 1-6 The prepolymer may be selected from the group consisting of 1, 2, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 51, 52, 53, 54, 55, 56, 57, 58, 59, 61, 62, 63, 64, 65, 67, 68, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95
[0029] The phase change layer and optionally one or both of the first cover layer and the second cover layer contain a plurality of boron nitride particles. The plurality of boron nitride particles may include one or both of a single particle (primary particle) or an agglomerate (secondary particle) containing a plurality of particles. The average particle size of the plurality of boron nitride particles (primary particles or agglomerates of particles) may be 0.1 micron to 1000 microns, or 5 microns to 500 microns, or 10 microns to 250 microns, or 25 microns to 150 microns, or 500 nanometers to 100 microns, or 3 microns to 40 microns. The plurality of boron nitride particles may include irregularly shaped hexagonal boron nitride flakes having an average particle size greater than or equal to 10 microns. As used herein, "particle size" refers to an average diameter or equivalent diameter that is preferably determined by standard laser particle measurement. Particle size may refer to a particle size known as the median diameter or the median diameter of a particle size distribution. 50 Particle size; it is the value of the particle diameter at 50% in the cumulative distribution by mass.
[0030] A plurality of boron nitride particles may be in the form of at least one of a powder (including flakes, small pieces, and other shapes), a fiber, a rod, a whisker, a sheet, a nanosheet, an agglomerate, or a boron nitride nanotube (BNNT), and may vary with crystal type, shape, and size, and include a certain distribution as described above. The average aspect ratio (ratio of the width or diameter of the particle to the length) of a plurality of boron nitride particles may be 1:2 to 1:100000, or 1:5 to 1:1000, or 1:10 to 1:300. Exemplary shapes of particles with particularly high aspect ratios include small pieces, rod-shaped particles, fibers, whiskers, and the like. A plurality of boron nitride particles may include boron nitride small pieces, for example, hexagonal boron nitride in the form of small pieces. The exact shape of the small piece is not critical. In this regard, the boron nitride small piece may have an irregular shape. It should be noted that the term "small piece" as used herein generally describes any thin, flat particle, including a thin piece. The average aspect ratio of the platelets (ratio of the width to the length of the particles) may be from 4:5 to 1:300, or from 1:2 to 1:300, or from 1:2 to 1:200, or from 3:5 to 1:100, or from 1:25 to 1:100.
[0031] About crystal type, boron nitride particles can include at least one structure in hexagonal structure, cubic structure, wurtzite structure, rhombohedral structure or other synthetic structures. In various structures, hexagonal boron nitride particles (hBN) can obtain excellent thermal conductivity of, for example, 10W / mK to 300W / mK or greater, and particles of cubic structure can obtain extremely high thermal conductivity of maximum 1300W / mK. The thermal conductivity of boron nitride particles can be determined according to ASTM E1225-13. Hexagonal boron nitride has a layered structure similar to graphite, wherein the layers are stacked in alignment so that the hexagonal rings in the layers overlap. The positions of N atoms and B atoms alternate layer by layer. Multiple boron nitride particles can have a hexagonal structure with a crystallization index of at least 0.12, or 0.20 to 0.55, or 0.30 to 0.55. Hexagonal boron nitride particles can be obtained from various commercial sources.
[0032] Crystalline or partially crystallized boron nitride particles can be made by methods known in the art. These include, for example, boron nitride powders produced by the pressing methods disclosed in U.S. Pat. Nos. 5,898,009 and 6,048,511, boron nitride agglomerated powders disclosed in U.S. Pat. No. 2005 / 0041373, and highly stratified boron nitride powders disclosed in U.S. Pat. No. 6,951,583. Various boron nitride powders are commercially available, for example from Momentive under the trade name POLARTHERMA TM Boron nitride is commercially available.
[0033] The plurality of boron nitride particles may include a coating. The coating may include at least one of carbon, aluminum, silicon, germanium, copper, nickel, palladium, platinum, iridium, cobalt, iron, ruthenium, molybdenum, tungsten, tantalum, zirconium, or titanium, for example in the form of at least one of a carbide, an oxide, a nitride, a sulfide, or a phosphide. The coating may include at least one of an inorganic carbide (e.g., aluminum carbide or titanium carbide), an inorganic oxide (e.g., aluminum oxide (Al2O3), magnesium oxide, silicon dioxide (SiO2), titanium dioxide, yttrium oxide, zirconium oxide, or zinc oxide), an inorganic nitride (e.g., aluminum nitride (AlN) or silicon nitride), an inorganic sulfide (e.g., gallium sulfide, molybdenum sulfide, or tungsten sulfide), an inorganic hydroxide (e.g., aluminum hydroxide ... x O y H z ), zinc hydroxide (Zn x O y H z ), or silicon hydroxide (Si x O y H z)), or an inorganic phosphide. The coating may include at least one of silicon dioxide or aluminum oxide. The coating may include one or more different coatings that may optionally be alternating layers. The coating may be applied to a plurality of boron nitride particles via atomic layer deposition (ALD). ALD is a type of chemical vapor deposition in which a thin film is deposited on a substrate using a vapor phase chemical precursor that reacts at the substrate surface.
[0034] The plurality of boron nitride particles may be surface treated with a coupling agent. The coupling agent promotes the formation of covalent bonds that improve the adhesion between the filler and the thermosetting polymer matrix or participates in the covalent bonds that improve the adhesion between the filler and the thermosetting polymer matrix. Exemplary coupling agents include silanes, zirconates, titanates, and the like, such as vinyl trichlorosilane, vinyl trimethoxysilane, trivinyl methoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy) silane, β-(3,4-epoxycyclohexyl) ethyl trimethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, N-β(aminoethyl)γ-aminopropyl trimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, N-β(aminoethyl)γ-aminopropyl triethoxysilane, γ-glycidoxypropyl triethoxysilane, N-β (Aminoethyl)γ-aminopropylmethyldimethoxysilane, bis(trimethoxysilylethyl)benzene, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, bis(triethoxysilyl)ethylene, triethoxysilyl-modified butadiene, styrylethyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, trimethoxyphenylsilane, perfluorooctyltriethoxysilane, or γ-mercaptopropyltrimethoxysilane.
[0035] Based on the total volume of the phase change layer, the phase change layer may include 5 volume % to 95 volume % or 50 volume % to 90 volume % of a plurality of boron nitride particles. Based on the volume of each covering layer, the first covering layer and the second covering layer may each independently include 0 volume % to 90 volume %, or 10 volume % to 80 volume %, or 30 volume % to 70 volume %, or 50 volume % to 70 volume % of a plurality of boron nitride particles. Based on the total volume of each covering layer, at least one of the covering layers may include more than 0 volume % to 90 volume %, or 30 volume % to 70 volume %, or 50 volume % to 70 volume % of a plurality of boron nitride particles.
[0036] The boron nitride particles in the phase change layer may be oriented. For example, the average angle of the boron nitride particles may be 0° to 45° or 10° to 35°, where the angle θ is measured along the vertical line, see Figure 1 .
[0037] The phase change material, the first cover layer, and the second cover layer may each independently contain additional fillers in addition to boron nitride, for example to adjust the dielectric properties of the layered phase change composite. Fillers with low expansion coefficients, such as glass beads, silica, or ground microglass fibers, may be used. Thermally stable fibers, such as aramid or polyacrylonitrile, may be used. Representative fillers include titanium dioxide (rutile and anatase), barium titanate, strontium titanate, fused amorphous silica, corundum, wollastonite, aramid fibers (e.g., KEVLAR from DuPont), and polyamide fibers (e.g., PTFE). TM ), glass fiber, Ba2Ti9O 20 , quartz, aluminum nitride, silicon carbide, beryllium oxide, alumina, magnesium oxide, mica, talc, nanoclays, aluminosilicates (natural and synthetic), and fumed silica (e.g., CAB-O-SIL from Cabot Corporation) TM ), each of which can be used alone or in combination.
[0038] Other fillers can be in the form of solid particles, porous particles or hollow particles. The particle size of other fillers affects many important characteristics, including thermal expansion coefficient, modulus, elongation and flame retardancy. The average particle size of other fillers can be 0.1 micron to 15 microns or 0.2 micron to 10 microns. The combination of fillers with bimodal, trimodal or higher average particle size distribution can be used. Based on the total volume of each layer, fillers can be included in the amount of 0.1 volume % to 80 volume % or 1 volume % to 65 volume % or 5 volume % to 50 volume %.
[0039] The phase change layer, the first cover layer, and the second cover layer may each independently contain additives, such as at least one of a flame retardant, a curing initiator, a crosslinking agent, a viscosity modifier, a wetting agent, or an antioxidant. The specific selection of additives may depend on the polymer used, the specific application of the layered phase change composite material, or the desired properties of the application, and may be selected so that the electrical properties are enhanced or not significantly adversely affected when used in a circuit subassembly, such as thermal conductivity, dielectric constant, dissipation factor, dielectric loss, or other desired properties.
[0040] The flame retardant can be inorganic and can be present in the form of particles. The inorganic flame retardant can include, for example, a metal hydrate having a volume average particle size of 1 nanometer (nm) to 500nm, or 1nm to 200nm, or 5nm to 200nm, or 10nm to 200nm; or, the volume average particle size can be 500nm to 15 microns or 1 micron to 5 microns. The metal hydrate can include a hydrate of at least one of a metal such as Mg, Ca, Al, Fe, Zn, Ba, Cu or Ni. Hydrates of Mg, Al or Ca can be used, such as at least one of aluminum hydroxide, magnesium hydroxide, calcium hydroxide, iron hydroxide, zinc hydroxide, copper hydroxide, nickel hydroxide, or a hydrate of calcium aluminate, dihydrate gypsum, zinc borate or barium metaborate. Composites of these hydrates can be used, such as hydrates containing at least one of Ca, Al, Fe, Zn, Ba, Cu or Ni and Mg. The composite metal hydrate can have the formula MgM x (OH) y , wherein M is Ca, Al, Fe, Zn, Ba, Cu or Ni, x is 0.1 to 10, and y is 2 to 32. The flame retardant particles may be coated or otherwise treated to improve dispersibility or other properties.
[0041] Organic flame retardants may be used instead or in addition to inorganic flame retardants. Examples of organic flame retardants include melamine cyanurate; fine particle size melamine polyphosphates; various other phosphorus-containing compounds, such as aromatic hypophosphites, diphosphites, phosphonates, phosphates; polysilsesquioxanes; siloxanes; or halogenated compounds (e.g., hexachloronadic acid (HET acid), tetrabromophthalic acid, or dibromoneopentyl glycol). Examples of brominated flame retardants include SAYTEX®, commercially available from Albermarle Corporation. TM BT93W (ethylene bis(tetrabromophthalimide)), SAYTEX TM 120 (tetradecabromodiphenoxybenzene) or SAYTEX TM 102 (decabromodiphenyl ether). Flame retardants can be used in combination with synergists, for example, halogenated flame retardants can be used in combination with synergists such as antimony trioxide, and phosphorus-containing flame retardants can be used in combination with nitrogen-containing compounds such as melamine.
[0042] The layered phase change composite material may be formed by: forming a first covering layer from a first composition; forming a phase change layer from a phase change composition, wherein forming the phase change layer comprises vibrating the phase change composition on a 3-way vibration table; and forming a second covering layer from a second composition. Forming the first covering layer and the second covering layer may each independently comprise vibrating each composition on a 3-way vibration table. Forming the phase change layer may comprise heating the phase change composition to a temperature greater than or equal to a phase change temperature.
[0043] The phase change composition may be free of solvent. For example, the phase change composition may contain 0 wt % to 0.5 wt % or 0 wt % of solvent based on the total weight of the phase change composition.
[0044] In one aspect, the layered phase change composite material may include: a phase change layer including a phase change material, a plurality of boron nitride particles, and a binder; and a first cover layer or both a first cover layer and a second cover layer located on opposite sides of the phase change layer. The phase change layer may include 1 volume % to 99 volume % of the phase change material, 5 volume % to 95 volume % of the plurality of boron nitride particles, and 0.5 volume % to 15 volume % of the binder, each based on the total volume of the phase change layer. The transition temperature of the phase change material may be -5°C to 150°C. The phase change material may include C 10-36 Alkanes, C 10-35 Fatty acids, C 10-35 At least one of fatty acid esters or vegetable oils. The boron nitride particles may include a plurality of hexagonal boron nitride flakes. The binder may include at least one of polystyrene, epoxy resin, polybutadiene or polyisoprene. The thickness of the phase change layer may be 0.05 mm to 10 mm, or 0.5 mm to 2 mm, or 0.5 mm to 1.5 mm, and the layer thickness of each of the covering layers may independently be 0.001 mm to 1 mm or 0.01 mm to 0.5 mm. Based on the total volume of each covering layer, the first covering layer and the second covering layer may each independently contain 10 volume % to 100 volume % of a binder such as epoxy resin, and optionally a plurality of hexagonal boron nitride flakes.
[0045] The layered phase change composite material can be formed by: forming a first covering layer from a first composition comprising a polymer and optionally a plurality of boron nitride particles; casting a curable composition comprising a phase change material and a first plurality of boron nitride particles on a 3-way vibration table, vibrating the table in three directions, and curing the curable composition hardener to form a phase change layer; and forming a second covering layer on the phase change layer from a second composition comprising a second polymer and optionally a second plurality of boron nitride particles.
[0046] The layered phase change composite material can be formed by casting a first curable composition comprising a first solvent and optionally a plurality of boron nitride particles on a 3-way vibration table, evaporating the first solvent while vibrating the table in three directions, and curing the first curable composition to form a first covering layer; casting a curable composition comprising a phase change material and a first plurality of boron nitride particles on a 3-way vibration table, vibrating the table in three directions, and curing the curable composition to form a phase change layer; and casting a second curable composition comprising a second solvent and optionally a second plurality of boron nitride particles on a 3-way vibration table, evaporating the second solvent while vibrating the table in three directions, and curing the second curable composition to form a second covering layer. The first curable composition may include a first epoxy resin and a first hardener. The second curable composition may include a second epoxy resin and a second hardener. The phase change composition may include a binder. It should be noted that the formation of the first covering layer and the second covering layer can be performed independently without vibration, especially when it does not contain a plurality of boron nitride particles.
[0047] Based on the gross weight of each composition, each of the first curable composition and the second curable composition can independently include 3 wt % to 50 wt % of the first solvent and the second solvent, respectively. The first solvent and the second solvent can independently include at least one of methanol, ethanol, isopropanol, butanol, xylene, toluene, methyl ethyl ketone, methyl isobutyl ketone, hexane, heptane, octane, nonane, cyclohexane, isophorone or a terpene-based solvent. Based on the gross weight of each covering composition, the first covering composition and the second composition can each independently include 3 wt % to 50 wt % of the solvent.
[0048] The layer of composite material can be formed in a layer-by-layer method, wherein a first covering layer is formed, a phase change layer is formed on the first covering layer, and a second covering layer is formed on the phase change layer. For example, forming the phase change layer may include casting a curable composition on the first covering layer, and forming the second covering layer may include casting a second curable composition on the phase change layer. On the contrary, forming the layer of the composite material may include forming a layered stack of a first covering layer, a phase change layer and a second covering layer, and then laminating the layered stack.
[0049] When vibration is used, the vibration may include vibrating each composition until the gel point is reached. The vibration may include vibrating in the z direction at a vibration frequency of 60 Hertz (Hz), wherein the vibration may be primarily in the z axis with vibration noise in the x and y directions.
[0050] The layers can be formed by spraying, air atomizing spraying, airless atomizing spraying, electrostatic spraying, slot die coating, contact slot coating, curtain coating, knife coating, roller coating, kiss coating, transfer coating, brushing, screen printing, padding, dipping, impregnation, printing, pressure or gravity feed nozzle / spray gun, hot melt coater, molding, overmolding, injection molding, reaction injection molding, pultrusion, extrusion, plasma coating, or using a resin infusion process (e.g., resin transfer molding (RTM), vacuum infusion process (VIP), or vacuum assisted RTM (VARTM)).
[0051] The first and second covering layers may each be formed independently by casting onto a carrier from which they are later released, or alternatively by casting onto a conductive metal layer (which may later be formed into a layer of a circuit structure).
[0052] After each layer is independently formed, the solvent (if present) can be evaporated. After each layer is independently formed, the layer (where applicable) can be at least partially cured (B stage), or the layer can be fully cured. Each layer can be independently partially cured initially, and then fully cured in the layered stack to promote adhesion between the layers. Each layer can be independently heated, for example, at 20°C to 200°C, or 30°C to 150°C, or 40°C to 100°C.
[0053] The layered phase change composite material may optionally include one or more additional layers. For example, there may be one or more additional phase change layers, and optionally additional cover layers. The composition may include, for example, an adhesive layer located between the phase change layer and the cover layer. In contrast, the phase change layer may be in direct physical contact with one or both of the first cover layer and the second cover layer.
[0054] The layered phase change composite material can provide improved thermal stability to the device, resulting in the ability to avoid performance and life degradation of the electronic device. The combination of boron nitride particles and phase change material can be advantageous for use as a thermal management material, especially in electronic devices, where the presence of the phase change material can allow a combination of high latent heat capacity and energy absorption, and the presence of boron nitride can increase the transfer rate of heat into and out of the phase change material, which can result in improved thermal management, lower heat accumulation, fewer problems and faster processor speeds.
[0055] The article may include the layered phase change composite material. The layered phase change composite material may be used in various applications, including electronic devices, LED devices or batteries. The layered phase change composite material may be used in various electronic devices and any other device that generates heat and damages the performance of processors and other operating circuits (memory, video chips or telecommunications chips). Examples of such electronic devices include mobile phones, personal digital assistants (PDAs), smart phones, tablet computers, laptop computers, handheld scanners or other general portable devices. The layered phase change composite material may be incorporated into virtually any electronic device that requires cooling during operation, such as electronic devices used in consumer products, medical devices, automotive components, aircraft components, radar systems, navigation systems or global positioning systems. The layered phase change composite material may be used in batteries, engine control units (ECUs), airbag modules, body temperature controllers, door modules, cruise control modules, dashboards, climate control modules, anti-lock brake modules (ABS), transmission controllers or power distribution modules. The layered phase change composite material and its article may also be incorporated into the housing of an electronic device or other structural component. In general, any device that relies on the performance characteristics of an electronic processor or other electronic circuit can benefit from the improved or more stable performance characteristics produced by utilizing aspects of the layered phase change composite material. In certain embodiments, the article is a thermal management material, a thermally conductive pad, an electrode for energy storage, a supercapacitor, a fuel cell, a battery, a capacitive desalination device, an acoustic insulator, a thermal insulation composite material, a chemical sensor, a mechanical sensor, a biomedical device, an actuator, an adsorbent, a catalyst carrier, a field emission device, a mechanical damping device, a filter, a three-dimensional flexible electronic component, a circuit material, an integrated circuit package, a printed circuit board, an electronic device, a cosmetic product, a wearable electronic device, a high-efficiency flexible electronic device, a power electronic device, a high-frequency device, or an energy storage device.
[0056] The layered phase change composite material can be incorporated into virtually any electronic device that requires cooling during operation. For example, electronic devices used in automotive components, aircraft components, radar systems, navigation systems, and GPS devices incorporated into civilian and military equipment and other vehicles can benefit from layered phase change composite materials, such as engine control units (ECUs), airbag modules, body controllers, door modules, cruise control modules, instrument panels, climate control modules, anti-lock brake modules (ABS), transmission controllers, or power distribution modules. Layered phase change composite materials and articles comprising the composite materials can also be incorporated into housings of electronic devices or other structural components. In general, any device that relies on the performance characteristics of an electronic processor or other electronic circuit can benefit from the improved or more stable performance characteristics produced by utilizing the aspects of the composite materials disclosed herein.
[0057] The following examples are provided to illustrate the present disclosure. The examples are illustrative only and are not intended to limit devices made according to the present disclosure to the materials, conditions or process parameters set forth herein.
[0058] Example
[0059] Example 1
[0060] The first covering layer is prepared by casting a composition comprising 20% by weight of isopropyl alcohol, 48% by weight of boron nitride particles and 32% by weight of a curable epoxy resin in a 3.3 cm diameter dish. The dish is then vibrated in the x-, y- and z-directions while the solvent is evaporated. After the solvent evaporates, the epoxy resin is cured to form the first covering layer. Vibration is stopped once the composition reaches the gel point.
[0061] Then, a phase change composition is cast on the first cover layer. The phase change composition comprises a mixture of 90 wt.% paraffin wax and 10 wt.% boron nitride and epoxy resin. The phase change composition is vibrated in the x-direction, the y-direction and the z-direction and the epoxy resin is cured to form a phase change layer. Figure 2 is a microscopic image of a top view of the phase change layer after curing. Figure 2 A domain 12 of boron nitride particles formed in the phase change layer is shown.
[0062] The second composition is then cast on the phase change layer. The second composition comprises 20% by weight of isopropanol, 48% by weight of boron nitride particles and 32% by weight of curable epoxy resin. The disk is then vibrated in the x-direction, y-direction and z-direction while the solvent is evaporated. After the solvent evaporates, the epoxy resin is cured to form a second covering layer. Once the composition reaches the gel point, vibration is stopped. The layered phase change composite is then dried at room temperature (approximately 20°C to 25°C) for 2 hours.
[0063] Figure 3 Scanning electron micrograph of a cross section of a layered phase change composite. Figure 3 The excellent orientation of the boron nitride particles in the phase change layer in the direction perpendicular to the broad surface of the composite material is shown.
[0064] Non-limiting aspects of the disclosure are set forth below.
[0065] Aspect 1: A layered phase change composite material, comprising: a phase change layer comprising a phase change material, a plurality of boron nitride particles and a binder; and a first cover layer and a second cover layer located on opposite sides of the phase change layer.
[0066] Aspect 2: The composite material according to aspect 1, wherein the phase change material comprises C 10-36 Alkanes, C 10-35 Fatty acids, C10-35 At least one of a fatty acid ester or a vegetable oil.
[0067] Aspect 3: A composite material according to any one or more of the preceding aspects, wherein the phase change layer comprises 1 volume % to 99 volume %, or 50 volume % to 99 volume %, or 80 volume % to 95 volume % of the phase change material based on the total volume of the phase change layer.
[0068] Aspect 4: The composite material according to any one or more of the preceding aspects, wherein the transition temperature of the phase change material is in the range of -5°C to 150°C.
[0069] Aspect 5: The composite material of any one or more of the preceding aspects, wherein the plurality of boron nitride particles comprises a plurality of hexagonal boron nitride platelets.
[0070] Aspect 6: The layered phase change composite material according to any one or more of the preceding aspects, wherein the phase change layer comprises 5 volume % to 95 volume % or 50 volume % to 90 volume % of the plurality of boron nitride particles based on the total volume of the phase change layer.
[0071] Aspect 7: The layered phase change composite material according to any one or more of the preceding aspects, wherein the binder comprises at least one of polystyrene, epoxy resin, polybutadiene, or polyisoprene.
[0072] Aspect 8: The layered phase change composite material according to any one or more of the preceding aspects, wherein the phase change layer comprises 0.5 to 15 volume % or 1 to 6 volume % of the binder based on the total volume of the phase change layer.
[0073] Aspect 9: The layered phase change composite material according to any one or more of the preceding aspects, wherein the thickness of the phase change layer is 0.05 mm to 10 mm, or 0.5 mm to 2 mm, or 0.5 mm to 1.5 mm.
[0074] Aspect 10: The layered phase change composite material according to any one or more of the preceding aspects, wherein the first cover layer and the second cover layer comprise epoxy resin.
[0075] Aspect 11: A layered phase change composite material according to any one or more of the preceding aspects, wherein the first covering layer and the second covering layer each independently contain 10 volume % to 100 volume %, or 30 volume % to 70 volume %, or 30 volume % to 50 volume % of a binder based on the total volume of each covering layer.
[0076] Aspect 12: The layered phase change composite material of any one or more of the preceding aspects, wherein at least one of the first cover layer and the second cover layer comprises a plurality of boron nitride particles.
[0077] Aspect 13: A layered phase change composite material according to any one or more of the preceding aspects, wherein at least one of the covering layers comprises 0 volume % to 90 volume %, or 30 volume % to 70 volume %, or 50 volume % to 70 volume % of a plurality of boron nitride particles based on the total volume of each covering layer.
[0078] Aspect 14: The layered phase change composite material according to any one or more of the preceding aspects, wherein the layer thickness of each of the cover layers is independently from 0.001 mm to 1 mm or from 0.01 mm to 0.5 mm.
[0079] Aspect 15: A layered phase change composite material according to any one or more of the preceding aspects, wherein the heat of fusion of the layered phase change composite material measured using thermogravimetric analysis is at least 50 J / g, or at least 75 J / g, or at least 100 J / g, or at least 50 J / g to 150 J / g.
[0080] Aspect 16: The layered phase change composite material according to any one or more of the preceding aspects, wherein the thermal conductivity of the composite material measured according to ASTM D5470-17 is greater than 0.5 W / mK, or is between 0.5 W / mK and 1 W / mK.
[0081] Aspect 17: The layered phase change composite material according to any one or more of the preceding aspects, further comprising a flame retardant.
[0082] Aspect 18: An article comprising the layered phase change composite material according to any one or more of the preceding aspects.
[0083] Aspect 19: The article according to Aspect 18, wherein the article is a thermal management material, a thermally conductive pad, an electrode for energy storage, a supercapacitor, a fuel cell, a battery, a capacitive desalination device, a sound insulator, a thermal insulation composite material, a chemical sensor, a mechanical sensor, a biomedical device, an actuator, an adsorbent, a catalyst carrier, a field emission device, a mechanical damping device, a filter, a three-dimensional flexible electronic component, a circuit material, an integrated circuit package, a printed circuit board, an electronic device, a cosmetic product, a wearable electronic device, a high-efficiency flexible electronic device, a power electronic device, a high-frequency device or an energy storage device.
[0084] Aspect 20: A method for manufacturing a layered phase change composite material according to any one or more of Aspects 1 to 17, comprising: forming a first covering layer from a first composition, wherein forming the first covering layer optionally includes vibrating the first composition on a 3-way vibration table; forming a phase change layer from a phase change composition, wherein forming the phase change layer includes vibrating the phase change composition on a 3-way vibration table; and forming a second covering layer from a second composition, wherein forming the second covering layer optionally includes vibrating the second composition on a 3-way vibration table; wherein each layer is formed independently and then stacked on top of each other to form the composite material, and / or wherein at least one of the layers is formed directly on one of the other layers.
[0085] Aspect 21: The method according to aspect 20, wherein the phase change composition is free of solvent.
[0086] Aspect 22: A method according to Aspect 20, wherein forming a first covering layer comprises casting a first composition comprising a first curable composition (e.g., comprising a first epoxy resin, a first hardener), a first solvent, and a first plurality of boron nitride particles on a 3-way vibration table, evaporating the first solvent while vibrating the table in three directions, and curing the first curable composition to form a first covering layer; wherein forming a phase change layer comprises casting a phase change composition comprising the phase change material, a curable composition (e.g., comprising an epoxy resin and a hardener), and the plurality of boron nitride particles on the 3-way vibration table, vibrating the table in three directions, and curing the curable composition to form a phase change layer; wherein forming a second covering layer comprises casting a second composition comprising a second curable composition (e.g., comprising a second epoxy resin and a second hardener), a second solvent, and a second plurality of boron nitride particles on a 3-way vibration table, evaporating the second solvent while vibrating the table in three directions, and curing the second curable composition to form a second covering layer.
[0087] Aspect 23: The method of aspect 22, wherein casting the phase change composition comprises casting the phase change composition onto the first cover layer.
[0088] Aspect 24: The method of any one or more of aspects 22 to 23, wherein casting the second composition comprises casting the second composition onto the phase change layer.
[0089] Aspect 25: The method of any one or more of aspects 22 to 24, wherein each of the casting steps independently comprises vibrating each composition until a gel point is reached.
[0090] Aspect 26: The method according to any one or more of Aspects 20 to 21, further comprising stacking the first cover layer, the phase change layer, and the second cover layer to form a layered stack, and laminating the layered stack.
[0091] Aspect 27: The method according to any one or more of Aspects 20 to 26, wherein each of the first composition and the second composition independently comprises 3 wt % to 50 wt % of the first solvent and the second solvent, respectively, based on the total weight of each composition.
[0092] Aspect 28: The layered phase change composite material according to any one or more of the preceding aspects, comprising: 1 volume % to 99 volume % of the phase change layer, and a first cover layer and a second cover layer located on opposite sides of the phase change layer, wherein the phase change layer comprises: 10-36 Alkanes, C 10-35 Fatty acids, C 10-35 A phase change material of at least one of fatty acid esters or vegetable oils; 5 volume % to 95 volume % of the plurality of boron nitride particles including a plurality of hexagonal boron nitride platelets; and 0.5 volume % to 15 volume % of the binder including at least one of polystyrene, epoxy resin, polybutadiene or polyisoprene. The thickness of the phase change layer can be 0.05 mm to 10 mm, or 0.5 mm to 2 mm, or 0.5 mm to 1.5 mm, and the layer thickness of each of the covering layers can independently be 0.001 mm to 1 mm or 0.01 mm to 0.5 mm. Based on the total volume of each covering layer, the first covering layer and the second covering layer can each independently contain 10 volume % to 100 volume % of the binder.
[0093] The compositions, methods and articles may alternatively include, consist of, or consist essentially of any suitable material, step, or component disclosed herein as any suitable material, step, or component disclosed herein. The compositions, methods and articles may additionally or alternatively be formulated without or essentially free of any material (or substance), step, or component that is not otherwise necessary to achieve the function or purpose of the compositions, methods and articles.
[0094] Unless the context clearly indicates otherwise, as used herein, an object without a quantifier and "at least one" do not indicate a limitation of quantity, and are intended to cover both the singular and the plural. For example, unless the context clearly indicates otherwise, "element" has the same meaning as "at least one element". The term "combination" includes blends, mixtures, alloys, reaction products, etc. In addition, "at least one of..." means that the list includes individual elements, as well as combinations of two or more elements in the list, and combinations of at least one element in the list with unspecified similar elements.
[0095] Unless the context clearly indicates otherwise, the term "or" means "and / or". References throughout the specification to "one aspect", "another aspect", "some aspects", etc. mean that a particular element (e.g., feature, structure, step, or characteristic) described with respect to the aspect is included in at least one aspect described herein, and may or may not be present in other aspects. In addition, it should be understood that the described elements may be combined in any suitable manner in multiple aspects.
[0096] Unless otherwise specified herein, all test standards are the latest standards valid as of the filing date of the present application or (if priority is required) as of the filing date of the earliest priority application in which the test standard appears. The endpoints of all ranges involving the same component or characteristic include the endpoints, can be independently combined, and include all intermediate points and scopes. For example, the scope of "up to 25 volume percents, or 5 volume percents to 20 volume percents" includes all intermediate values of the endpoint and "5 volume percent to 25 volume percent" scope, such as 10 volume percent to 23 volume percents, etc. As used herein, the terms "first", "second", etc. do not represent any order, quantity or importance, but are used to distinguish one element from another element. When an element such as a layer, film, region or substrate is referred to as "on" another element, it can be directly on another element, or there can also be an intermediate element. In contrast, when an element is referred to as "directly on" another element "on" or "directly physically contacting" another element, there is no intermediate element.
[0097] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0098] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in the present application contradicts or conflicts with a term in the incorporated reference, the term in the present application takes precedence over the conflicting term in the incorporated reference.
[0099] Although specific embodiments have been described, the applicant or other persons skilled in the art may conceive of alternatives, modifications, variations, improvements, and substantial equivalents that are not currently foreseeable or may not currently be foreseeable. Therefore, the appended claims, as filed and as may be amended, are intended to cover all such alternatives, modifications, improvements, and substantial equivalents.
Claims
1. A layered phase change composite material comprising: a phase change layer comprising a phase change material, a plurality of boron nitride particles and a binder; as well as a first cover layer and a second cover layer located on opposite sides of the phase change layer, Wherein, based on the total volume of the phase change layer, the phase change layer contains 50 volume percent to 99 volume percent of the phase change material, and The boron nitride particles in the phase change layer are oriented.
2. The layered phase change composite material according to claim 1, wherein the phase change material comprises C 10-36 Alkanes, C 10-35 Fatty acids, C 10-35 At least one of a fatty acid ester or a vegetable oil.
3. The layered phase change composite material according to claim 1 or 2, wherein the phase change layer comprises 80 volume percent to 95 volume percent of the phase change material based on the total volume of the phase change layer, and wherein the average angle of the oriented boron nitride particles in the phase change layer is 0° to 45°, and the average angle is measured relative to the direction perpendicular to the wide surface of the composite material.
4. The layered phase change composite material according to claim 1 or 2, wherein the transition temperature of the phase change material is -5 degrees Celsius to 150 degrees Celsius.
5. The layered phase change composite material according to claim 1 or 2, wherein at least one of the plurality of boron nitride particles comprises a plurality of hexagonal boron nitride platelets; or the binder comprises at least one of polystyrene, epoxy resin, polybutadiene or polyisoprene.
6. The layered phase change composite material according to claim 1 or 2, wherein the phase change layer comprises 50 volume percent to 90 volume percent of the plurality of boron nitride particles based on the total volume of the phase change layer, and wherein the average angle of the oriented boron nitride particles in the phase change layer is 10° to 35°, and the average angle is measured relative to a direction perpendicular to a wide surface of the composite material. 7 . The layered phase-change composite material according to claim 1 , wherein the phase-change layer comprises 0.5 volume percent to 15 volume percent of the binder based on the total volume of the phase-change layer.
8. The layered phase-change composite material according to claim 1 or 2, wherein the phase-change layer comprises 1 volume percent to 6 volume percent of the binder based on the total volume of the phase-change layer.
9. The layered phase-change composite material according to claim 1 or 2, wherein the thickness of the phase-change layer is 0.05 mm to 10 mm; and wherein the layer thickness of each of the cover layers is independently 0.001 mm to 1 mm. 10 . The layered phase change composite material according to claim 9 , wherein the thickness of the phase change layer is 0.5 mm to 2 mm.
11. The layered phase change composite material according to claim 9, wherein the thickness of the phase change layer is 0.5 mm to 1.5 mm. 12 . The layered phase-change composite material according to claim 9 , wherein the layer thickness of each of the cover layers is independently 0.01 mm to 0.5 mm.
13. The layered phase change composite material according to claim 1 or 2, wherein the first cover layer and the second cover layer comprise epoxy resin.
14. The layered phase change composite material according to claim 1 or 2, wherein the first covering layer and the second covering layer each independently contain: 10 volume percent to 100 volume percent of a binder based on the total volume of the corresponding covering layer; and 0 volume percent to 90 volume percent of a plurality of boron nitride particles based on the total volume of the corresponding covering layer. 15 . The layered phase change composite material according to claim 14 , wherein the first cover layer and the second cover layer each independently comprise: 30 volume percent to 70 volume percent of a binder based on the total volume of the corresponding cover layer.
16. The layered phase change composite material according to claim 14, wherein the first cover layer and the second cover layer each independently comprise: 30 volume percent to 50 volume percent of a binder based on the total volume of the corresponding cover layer.
17. The layered phase-change composite material according to claim 14, wherein the first cover layer and the second cover layer each independently comprise: 30 volume percent to 70 volume percent of a plurality of boron nitride particles based on the total volume of the corresponding cover layer.
18. The layered phase-change composite material according to claim 14, wherein the first cover layer and the second cover layer each independently comprise: 50 volume percent to 70 volume percent of a plurality of boron nitride particles based on the total volume of the corresponding cover layer.
19. The layered phase change composite material of claim 1 or 2, wherein the heat of fusion of the layered phase change composite material measured using thermogravimetric analysis is at least 50 J / g; or wherein the thermal conductivity of the layered phase change composite material measured according to ASTM D5470-17 is greater than 0.5 Watts / meter Kelvin.
20. The layered phase change composite material of claim 1 or 2, wherein the layered phase change composite material has a heat of fusion of at least 75 J / g as measured using thermogravimetric analysis.
21. The layered phase change composite material of claim 1 or 2, wherein the layered phase change composite material has a heat of fusion of at least 100 J / g as measured using thermogravimetric analysis.
22. The layered phase change composite material according to claim 1 or 2, wherein the heat of fusion of the layered phase change composite material measured using thermogravimetric analysis is 50 J / g to 150 J / g.
23. The layered phase change composite material according to claim 1 or 2, wherein the thermal conductivity of the layered phase change composite material measured according to ASTM D5470-17 is 0.5 Watts / meter Kelvin to 1 Watts / meter Kelvin.
24. An article comprising a layered phase change composite material according to any one of the preceding claims.
25. The article of claim 24, wherein the article is a thermally conductive pad, an electrode for energy storage, a supercapacitor, a fuel cell, a capacitive desalination device, a sound insulator, a thermal insulation composite material, a chemical sensor, a mechanical sensor, a biomedical device, an actuator, an adsorbent, a catalyst carrier, a field emission device, a mechanical damping device, a filter, a three-dimensional flexible electronic component, an integrated circuit package, a printed circuit board, a cosmetic product, a wearable electronic device, a high-efficiency flexible electronic device, a power electronic device, or a high-frequency device.
26. The article of claim 24, wherein the article is a thermal management material, a circuit material, a battery, an electronic device, or an energy storage device.
27. A method for manufacturing a layered phase change composite material according to any one of claims 1 to 23, comprising: forming a first cover layer from a first composition, wherein forming the first cover layer optionally comprises vibrating the first composition on a 3-way vibration table; forming a phase change layer from a phase change composition, wherein forming the phase change layer comprises vibrating the phase change composition on a 3-way vibration table; and forming a second cover layer from a second composition, wherein forming the second cover layer optionally comprises vibrating the second composition on a 3-way vibration table; and The respective layers are each independently formed and then stacked on each other to form the composite material, and / or at least one of the respective layers is directly formed on one of the other layers.
28. The method of claim 27, wherein the phase change composition is free of solvent.
29. The method according to claim 27, wherein forming the first covering layer comprises casting a first composition comprising a first curable composition, a first solvent, and a first plurality of boron nitride particles on a 3-way vibration table, evaporating the first solvent while vibrating the 3-way vibration table in three directions, and curing the first curable composition to form the first covering layer; wherein forming the phase change layer comprises casting a phase change composition comprising the phase change material, a curable composition and the plurality of boron nitride particles on the 3-way vibration table, vibrating the 3-way vibration table in three directions, and curing the curable composition to form the phase change layer; The forming of the second covering layer includes casting a second composition comprising a second curable composition, a second solvent, and a second plurality of boron nitride particles on a 3-way vibration table, evaporating the second solvent while vibrating the 3-way vibration table in three directions, and curing the second curable composition to form the second covering layer.
30. The method of claim 29, wherein the first curable composition comprises a first epoxy resin and a first hardener, and / or wherein the curable composition comprises an epoxy resin and a hardener when forming the phase change layer, and / or The second curable composition comprises a second epoxy resin and a second hardener.
31. The method of claim 29 or 30, wherein casting the phase change composition comprises casting the phase change composition onto the first cover layer.
32. The method of claim 29 or 30, wherein casting the second composition comprises casting the second composition onto the phase change layer.
33. The method of claim 29 or 30, wherein each of the casting steps independently comprises vibrating the respective composition until a gel point is reached.
34. The method according to any one of claims 27 to 30, further comprising stacking the first cover layer, the phase change layer, and the second cover layer to form a layered stack, and laminating the layered stack.
Citation Information
Patent Citations
Boron nitride agglomerated powder
US20050041373A1
High density agglomerated boron nitride particles
US5898009A
Method for forming high density boron nitride and high density agglomerated boron nitride particles
US6048511A
Highly delaminated hexagonal boron nitride powders, process for making, and uses thereof
US6951583B2
Compressible thermal interface material
CN105980512A